Electrical Engineering Stack Exchange is a question and answer site for electronics and electrical engineering professionals, students, and enthusiasts. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

So I'm currently studying Electronic Devices and Circuit Theory by Boylestad and Nashelsky (11th ed.) and I'm confused as to how the relation between \$I_{CEO}\$ and \$I_{CBO}\$ is derived. So the derivation in the book starts with the equation $$I_C = \alpha I_E + I_{CBO}\ \tag1$$ But since \$I_E = I_C + I_B\$ , $$I_C = \alpha (I_C + I_B) + I_{CBO}\ \tag2$$ Rearranging yields $$I_C = \frac{\alpha I_B}{1-\alpha} + \frac{I_{CBO}}{1-\alpha}\ \tag3$$ Then it goes on to say that \$I_C\$ when \$I_B = 0\$ is assigned the notation \$I_{CEO} = \frac{I_{CBO}}{1-\alpha} \approx \beta I_{CBO}\$ which is consistent with other sources.

The weird thing I noticed is that letting \$\alpha I_E = I_C\$ in eq. 1 produces $$I_C = I_C + I_{CBO}\ \tag4$$ and letting \$ \frac{\alpha I_B}{1-\alpha}=\beta I_B = I_C\$ in eq. 3 produces $$I_C = I_C + \frac{I_{CBO}}{1-\alpha}\ \tag5$$ which are surprisingly not the same in addition to being paradoxy/fallacious... So my question is what went wrong?

share|improve this question
up vote 5 down vote accepted

The original equations are: $$I_C = \alpha I_E + I_{CBO} \tag{a}$$ $$I_C = \beta I_B + (\beta +1)I_{CBO} \tag{b}$$

Before equation 4, you mentioned that \$\alpha I_E = I_C\$. But this is valid only when \$I_{CBO} = 0\$ and that is what equation 4 says.

In the same way, \$I_C = \beta I_B\$ is valid only if \$I_{CBO} = 0\$ and that is what equation 5 says.

Both equation 4 and 5 are valid only under the approximation that \$I_{CBO} = 0\$.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.